Perfil microbilógico de diferentes tipos de saladas provenientes de cozinhas hospitalares - Correia, Letícia Borges Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Vegetables crops are indispensable items in human diet, acting as adjuvants in the prevention and treatment of diseases. However, the number of Foodborne Diseases outbreaks associated with their consumption increases. The aim of this study was determine the microbiological profile of different salads from hospital kitchens. In the period between 2010 and 2014 the Public feeding orientation service (SOAP) received 641 samples of salads from hospital kitchens in the region of Botucatu and Bauru. They, where subjected to microbiological analysis to determine the most probable number of coliforms at 35 ° C and 45 ° C, besides Salmonella spp presence and coagulase-positive staphylococci counts. The results reveal that 30.56% of the samples had counts for coliform at 35°C greater than 1.100 MPN/g and 12.17% had MPN/g of coliforms at 45°C above 100 MPN/g, the maximum limit established by Brazilian legislation. The prevalence of samples without heat treatment was 2.56% and 97.44% with heat treatment, cooked or braised. All samples were negative for Salmonella spp count and coagulase positive staphylococci < 1,0x102 UFC/g. Although most salads had an adequate microbiological quality, attention should be paid to the safety indicators as the meals are served to hospitalized individuals

As hortaliças são itens indispensáveis na dieta dos seres humanos, atuando como adjuvantes na prevenção e tratamento de doenças. Porém, destaca-se o aumento de surtos de Doenças Transmitidas por Alimentos (DTA) associados ao consumo de produtos hortícolas. O objetivo desse trabalho foi verificar o perfil microbiológico de diferentes tipos de saladas de cozinhas hospitalares. No período de 2010 a 2014, o Serviço de Orientação a Alimentação Pública (SOAP) recebeu 641 amostras de saladas provenientes de hospitais da região de Bauru e Botucatu, onde foram submetidas às análises microbiológicas para a determinação do número mais provável de coliformes a 35°C e 45°C, pesquisa de Salmonella spp e contagem de estafilococos coagulase positiva. Os resultados revelaram que em 30,56% das amostras a contagem de coliformes a 35°C foi maior que 1.100 NMP/g e 12,17% apresentaram coliformes a 45°C acima de 100 NMP/g, limite máximo estabelecido pela legislação brasileira. A prevalência de amostras contaminadas sem tratamento térmico foi de 97,44% e de 2,56% para amostras com tratamento térmico, cozidas ou refogadas. Todas as amostras foram negativas para presença de Salmonella spp e apresentaram contagem de estafilococos coagulase positiva < 1,0X102 UFC/g. Apesar das amostras de saladas não oferecerem risco microbiológico associado à patógenos, deve-se atentar para os micro-organismos indicadores, pois as refeições são servidas a indivíduos hospitalizados
Microbiological profile of different types of salad from hospital kitchens
Keywords: Hortaliças; Diagnóstico microbiológico; Hospitais - Serviço de alimentação; Estafilococos; Coagulase; Salmonella; Vegetables; Diagnostic microbiology